Creation of an algorithm and software complex for solving parabolic type boundary value problems by statistical modeling method (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The constant and unrelenting interest in the application of statistical modeling (Monte Carlo methods) both for research purposes and for solving practical problems is due to many factors. First of all, Monte Carlo methods are used for computational experiments to determine the properties of such phenomena for which the probabilistic model is, on the one hand, the most adequate and, at the same time, quite effectively implemented